(untitled) (KULT_online, 2011)
While discussing the spatial turn, it’s not only space, but also place, that is a decisive category. However, since the arts generally deal in fantastic and imaginary figures, one has to cope with phenomena that cannot be localized geographically. In order to augment the conceptual tools, this edited volume introduces "counterplaces" as a new concept in cultural studies. Moreover, and bridging the gap between fields of space research, the articles are meant to highlight narrative and performative modes that emphasize the modelling of places as a way of shaping works of art. Nevertheless, the applicability of the concept itself within cultural studies remains vague.